2008
DOI: 10.1590/s0100-54052008000300018
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de fungicidas no controle de Fusarium graminearum, germinação, emergência e altura de plântulas em sementes de trigo

Abstract: The effect of chemical treatment of wheat seeds (cv. "BR 18 Terena") was studied under laboratory and greenhouse conditions using the following fungicides with the respective doses of i.a./100 kg of seeds: captan (150 g), methilic tioafanate (75 mL), triflumizole (45 g), triticonazole (45 mL) triadimenol (13.5 mL), tolyfluanid (75 g), tebuconazole (5 mL), fludioxonil (5 mL), difeconazole (30 mL) and thiabendazole (30 mL). In laboratory, seeds health and germination were evaluated while under greenhouse conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 1 publication
1
4
0
4
Order By: Relevance
“…Garcia Júnior et al (2008) found no phytotoxic effect of this fungicide on wheat seeds, verifying germination and seedling emergence similar to untreated control seeds, as observed by Mendes et al (2001) with alfalfa seeds and Gally et al (2004) with soybean seeds. Yet, Fessel et al (2003) reported that a very high concentration of fungicide could impair maize seed quality.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Garcia Júnior et al (2008) found no phytotoxic effect of this fungicide on wheat seeds, verifying germination and seedling emergence similar to untreated control seeds, as observed by Mendes et al (2001) with alfalfa seeds and Gally et al (2004) with soybean seeds. Yet, Fessel et al (2003) reported that a very high concentration of fungicide could impair maize seed quality.…”
Section: Resultssupporting
confidence: 78%
“…and Rhizopus sp. in castor bean seeds (David et al, 2014), Leptosphaeria maculans in cabbage seeds (Maude et al, 1984), Fusarium graminearum in wheat seeds (Garcia Júnior et al, 2008), Fusarium moniliforme (Pinto, 2000) and Stenocarpella maydis (Carvalho et al, 2004) in maize seeds. These studies demonstrate that Thiabendazole is effective in controlling fungi in seeds of different species, as observed in the present study with melon seeds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of rainfall during the harvest period contribute to the infection of seeds [34]. Infected seed dispersal is characterized as the main source of inoculum, briefly rendering the cultivation unfeasible [20]. In our study, comparison was made only between herbicide treatments and TWA.…”
Section: Discussionmentioning
confidence: 99%
“…Assim também, os danos causados pelas espécies de Aspergillus e Penicillium são variáveis, como: diminuição de germinação, descoloração das sementes, aumento da taxa de ácidos graxos, aquecimento da massa de sementes e produção de toxinas (Choudhury, 1987;Lucca-Filho, 1995). Neste sentido, García-Junior et al (2008) relataram que a presença de F. graminearum em sementes de trigo, poderia resultar em uma maior percentagem de sementes mortas, reduzindo a percentagem de germinação de sementes no campo. É importante lembrar que diferentes valores de densidade de inóculo para patógenos transmitidos por sementes, geralmente, apresentam diferentes implicações epidemiológicas, pois altas densidades de inóculo em sementes constituem-se, certamente, em maiores riscos de ocorrência de danos no campo de cultivo (Machado, 2000).…”
Section: Tabelaunclassified